15. IMPORTANCE OF SPIRITUAL IDEAS IN YOUTH EDUCATION - Salimov Bakhriddin Lutfullaevich. Abdinazarov Sukhrobbek Farkhodovich. (Innovative technologies in construction Scientific Journal, 2023)
The article analyzes the importance of spiritual ideas in many works of art created by talented writers in the education of the young generation, and in particular, the ideas expressed in the works of one of the great figures of Uzbek literature, Musa Tashmuhammad son of Oibek, have not lost their importance even today.